Haematological parameter evaluation in different types of deletional alpha thalassaemia and in coinheritance of deletional alpha thalassaemia and beta thalassaemia in Hospital Universiti Sains Malaysia - Arifin, Samilawati Mohd (2018)
Alpha thalassaemia is a common genetic disorder in Malaysia and is a public health problem. Effective screening tool is an essential element in Thalassaemia Prevention and Control Programme to effectively detect all cases of thalassaemia and to maximize the resources. The aim of this study was to evaluate the haematological parameters in various types of deletional alpha (α) thalassaemia and effect of coinheritance with beta (β) thalassaemia towards the haematological parameters among patients in Hospital Universiti Sains Malaysia (HUSM), Kelantan, Malaysia. A cross-sectional study with retrospective record review on 214 samples sent to Molecular Unit, Hematology Unit, HUSM was conducted. A permission from Director of HUSM was obtained. The data was analyzed to study the red cell indices (haemoglobin concentration, red blood cell (RBC) count, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), red cell distribution width (RDW) and platelet count in various spectrum of α thalassaemia and in coinheritance cases. Seventy one (33.2%) cases were detected to have deletional α thalassaemia. The most common type detected was South-East Asian (SEA) type deletion (αα/--SEA), α thalassaemia (50.7%). Coinheritance of α thalassaemia with β thalassaemia/haemoglobinopathy was seen in 13.8% ofcases with the most common coinheritance was seen between SEA heterozygous (αα/--SEA) with codon 26 mutation (HbE). There were significant differences of RBC count, MCV and MCH level in patients with deletional α thalassemia compared to group without α gene deletion (p-value < 0.001). Deletional α thalassaemia cases showed median MCH level of 20.8 fL. The MCV and RBC counts gave an added value in differentiating between the group and might aid in making the diagnosis if the molecular technique is not available. Significant haematological differences include haemoglobin concentration, MCV, MCH, RDW and platelet count were observed among 3 commonest spectrum of deletional α thalassaemia which is between 3.7 heterozygous, SEA heterozygous and 3.7 heterozygous with SEA heterozygous. The parameters can be used as a good screening tool before persuing molecular testing in order to reduce the overall financial burden of diagnostic testings.